2013
DOI: 10.1186/1471-2393-13-64
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric fistula in Southern Sudan: situational analysis and Key Informant Method to estimate prevalence

Abstract: BackgroundObstetric fistula is a severe condition which can have devastating consequences for a woman’s life. Despite a considerable literature, very little is known about its prevalence. This project was conducted to carry out a situational analysis of fistula services in South Sudan and to pilot test the Key Informant Method (KIM) to estimate the prevalence of fistula in a region of South Sudan.MethodsKey stakeholder interviews, document reviews and fistula surgery record reviews were undertaken. A KIM surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…A 2013 systematic review and meta‐analysis found only ten studies that used clinically confirmed cases to estimate community‐based OF prevalence; four of these were conducted in sub‐Saharan Africa or South Asia . Subsequent to the review, two population‐based cross‐sectional studies from southern Sudan and Pakistan used confirmatory clinical examinations; however, neither of these studies used a control population to assess the validity of the screening questions used to identify cases . At present, there is no widely used, well‐validated fistula screening tool.…”
Section: Introductioncontrasting
confidence: 82%
See 1 more Smart Citation
“…A 2013 systematic review and meta‐analysis found only ten studies that used clinically confirmed cases to estimate community‐based OF prevalence; four of these were conducted in sub‐Saharan Africa or South Asia . Subsequent to the review, two population‐based cross‐sectional studies from southern Sudan and Pakistan used confirmatory clinical examinations; however, neither of these studies used a control population to assess the validity of the screening questions used to identify cases . At present, there is no widely used, well‐validated fistula screening tool.…”
Section: Introductioncontrasting
confidence: 82%
“…The OF prevalence estimates from other population‐based studies with confirmatory clinical examinations from sub‐Saharan Africa and South Asia vary widely, and were significantly higher than those found in our study: 162 per 100 000 women (95% CI 153–264) in Ethiopia ( n = 19 153); 95 per 100 000 women (95% CI 2–526) in Gambia ( n = 1038); 30 per 100 000 women (95% CI 10–100) in Southern Sudan ( n = 8865); 86 per 100 000 (95% CI 2–480) in Maharashtra, India ( n = 1167); 260 per 100 000 (95% CI 7–1439) in Karnataka, India; and 390 per 100 000 women (95% CI 220–570) or 450 per 100 000 parous women (95% CI 250–650) in Pakistan ( n = 5064) . Notably, these studies used different sampling methodologies and none of the studies examined controls (women who did not report symptoms of OF).…”
Section: Discussionmentioning
confidence: 99%
“…Once articles included in the review were compiled, researchers reviewed details of the articles and grouped them into five categories based on the extent to which the article discussed barriers to fistula treatment: 1 Barriers are the primary focus of the study 2 Article identifies factors that the reviewers perceived as barriers 3 Barriers are mentioned briefly in introduction or discussion, and barriers are not the primary focus of the article 4 Reviews/needs assessments/annual reports with some mention of barriers 5 Interventions aiming to remove barriers to fistula treatment Based on barriers identified by articles included in the review, the reviewers looked for similarities and differences between barriers to break them down into groups. Nine themes emerged: (1) psychosocial, (2) cultural, (3) awareness, (4) social, (5) financial, (6) transportation, (7) facility shortages, (8) quality of care and (9) political leadership.…”
Section: Categorising Studies and Barriersmentioning
confidence: 99%
“…Determining the number of women suffering with fistula worldwide is difficult, however, as many of these women are marginalised from society with little economic, social or political power. A recent systematic review found a pooled prevalence of 0.29 cases of fistula per 1000 women of reproductive age, and a pooled incidence of 0.09-0.66 new cases of fistula per 1000 recently pregnant women each year [7]. These data suggest approximately one million women with fistula in sub-Saharan Africa and South Asia and more than 6000 new cases per year in these two world regions [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation